Freedom of Thinking in the Terms of Virtualization of the Technological Environment. / Libertad de pensamiento en términos de virtualización del entorno tecnológico - Lukyanenko, Anton A. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The article deals with determining the specificity of the representation of the phenomenon of freedom in the mind of the subject when interacts with objects of virtual reality. On the basis of phenomenological research, the author claims that the essential characteristic of the representation of the phenomenon of freedom in the mind, when interacting with virtual reality, is the intention to superiority, not only over natural and spiritual laws but over principles of categorical thinking. A person, when interacting with virtual reality, represents freedom as a value setting expressing the desire for superiority over the existing social logos.RESUMEN El artículo trata de determinar la especificidad de la representación del fenómeno de la libertad en la mente del sujeto cuando interactúan administradores con objetos de la realidad virtual. Sobre la base de la investigación fenomenológica, el autor afirma que la característica esencial de la representación del fenómeno de la libertad en la mente, al interactuar con la realidad virtual, es la intención de la superioridad, no sólo sobre las leyes naturales y espirituales, sino sobre los principios del pensamiento categórico. Una persona, al interactuar con la realidad virtual, representa la libertad como un valor que expresa el deseo de superioridad sobre los logos sociales existentes.